Versatile Protein Coronation Approach with Multiple Depleted Serum for Creating Biocompatible, Precision Nanomedicine. Issue 30 (1st July 2022) - Wang, Chan; Xue, Mengdie; Liu, Xiao; Chen, Jingjing; Jiang, Mengdie; Zheng, Liuting; Ma, Ruxuan; Ding, Chengjin; Tao, Yaping; Zhang, Hao; Liu, Qin; Huo, Da
Abstract: The protein corona effect has long been treated as the evil source behind delivery efficacy issues. In this study, this concept is challenged by showcasing that the protein corona can serve as a versatile functionalization approach to improve the delivery efficacy or mitigate nanocytotoxicity. To this end, the depleted serum is introduced to create nanomaterials carrying functionally distinct protein corona, referred to as PCylated nanomaterials. It is confirmed that the passivation with depleted serum helps reduce the toxicity and pro‐inflammatory response. Furthermore, the same method can be leveraged to enhance the capacity of nanomaterials to undergo endocytosis as well as their potential as an agonist for the NF‐κB pathways. The comparable stability of protein corona created by late and early‐stage serum reveals that the chanceless interaction with nanomaterials, rather than an inadequate binding strength, may be behind the failure of enriching certain components. The PCylation strategy is extended to cancer patient‐derived fluid, creating a set of T1 and T3‐stage cancer‐specific nanotherapeutics to retard the metastasis of cancer cells, while leaving normal endothelial negligibly affected. It is hoped the novel PCylation approach validated here can shed light on the future development of precision nanomedicine with improved delivery efficacy. Abstract : In this study, it is reported that the depleted serum can be harnessed to functionalize nanomaterials, namely the PCylation strategy, through which several issues like cytotoxicity or insufficient cellular uptake can be greatly mitigated. Furthermore, with the combination of patient‐derived fluid, and the values of PCylated nanomaterials for prognosis prediction and for precision treatment are consolidated.